Social movements in globalization, new technologies and Public Administration - Candela Talavero, José Enrique (2019)
The social movements configures nowadays as political collective actors, whose claims, in whose claims are presented elements of the current phenomenon of globalization because of the interrelationship that they cause globally and the utilization in their pretensions of the mass media on one hand and of Internet, or of the social networks on the other one, in the new technological age. This phenomenon provokes a a leap from the local to the global; from the location of a problem in a territory to the leap in the international scale of a certain pretensionRight connected with the fact that, in the current era of “Facebook”, also the Administration adapts to these advances in its different fields of action: the administrative Process, Urbanism, public Contracts, tax system and taxation, Cadastre, National Health Service, protection of Information of personal character, the electoral regime, the electronic signature, Justice. In doing so, the system thereby seek to give citizens the right to good administration and simultaneously to satisfy the general interests.